Neither true-friend nor fairweather friend: Relationship banking and SME borrowing under Covid-19 - Tianshu Zhao; Kent Matthews; Max Munday (Cardiff University, Cardiff Business School, 2021)
A growing literature addresses the costs and benefits associated with relationship banking, articularly for smaller firms, but with much of this work focused on normal trading conditions. Covid-19 rovides an ideal testbed to explore the resilience of relationship banking. We examine whether the presence of closer pre-Covid ties between SMEs and their banks helps in accessing funds in the Covid-19 pandemic period. Then are ties between relationship bankers and SME borrowers a case of `true love' or rather are the parties more akin to `fair-weather friends'? Data from the UK SME Finance Monitor from 2018Q2-2020Q3 is used to examine this question. Our analysis suggests that relationship banking was important for the acquisition of bank credit pre-Covid-19 but was of limited influence in post-Covid-19 lending behaviour. Banks treated SMEs that had a good relationship with them in the same way as those that did not and with public interventions to support lenders material in this.
Keywords: G21; G28; G40; 330; Covid-19; Relationship Banking; SMEs